Evaluation of infrapatellar tendon plication in spastic cerebral palsy with crouch gait pattern: a pilot study - Tageldeen Mohamed Mohamed (SICOT-J, 2020)
Objective: In order to substantially improve crouch pattern in cerebral palsy, the existent patella alta needs to be addressed. This pilot study evaluates the effectiveness of a previously described infrapatellar tendon plication for the treatment of patella alta in crouch gait pattern in skeletally immature spastic cerebral palsy patients. Methods: In 10 skeletally immature patients (20 knees) with spastic diplegia and crouch gait, the previously described technique by Joseph et al. for infrapatellar tendon plication was evaluated within the setting of single event multilevel surgery (SEMLS). Outcome measures included knee extension lag, Koshino’s radiological index for patella alta, and the occurrence of complications. Patients were followed-up for a minimum of 12 months. Results: The extensor lag improved and was statistically significant in all cases of the study with no incidence of tibial apophyseal injury at the latest follow-up. Radiographic Koshino index normalized and was maintained all through the follow-up period except in one patient (5%) who was overcorrected. Two patients (4 knees, 20%) showed postoperative knee stiffness due to casting which resolved with physiotherapy within six weeks. One knee (5%) developed a superficial infection which also resolved uneventfully with repeated dressings. Conclusion: The described infra-patellar plication technique in skeletally immature spastic diplegics appears effective, safe, and reproducible.